Deep Vein Thrombosis (DVT): A Literature Review - Kamila, Alya Syafa; Ginuluh, Gintis Dhimar; Syakir, Syahda Aqila; Abida, Aisya Nur; Balqis, Ananda Amirah; Karlina, Fairuz; Murniatin, Rinesita; Farras, Afif; Raihan, Al Fikar; Putra, Rian Akka Jaya; Arsyatt, Maz Isa Ansyori (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Deep Vein Thromboembolism (DVT) occurs due to the formation of blood clots in the veins, characterized by the formation of thrombi along with an inflammatory response in the inner walls of the veins. DVT most commonly occurs in the deep veins of the lower extremities but can also occur, albeit less frequently, in other areas such as the arms or other forms of superficial thrombosis. This article aims to review the epidemiology, clinical presentation, diagnosis, pathophysiology, and management of deep vein thrombosis. The literature review was conducted by searching for relevant articles on deep vein thrombosis published in the past fifteen years. Literature searches were performed using Google Scholar, PubMed, and NCBI databases. The findings highlight the clinical manifestations of DVT and its potential to cause serious complications, particularly post-thrombotic syndrome. Post-thrombotic syndrome is a debilitating condition that can significantly impair patients' quality of life. Management of DVT involves both pharmacological and non-pharmacological treatments. Understanding the mechanisms of deep vein thrombosis and its management is crucial in minimizing the complications associated with this condition.